Unsteady mixed convection flow over a cylinder of elliptic cross section near forward stagnation point - Jamaludin, Madina (Faculty of Science, Universiti Teknologi Malaysia, 2012)
The unsteady mixed convection ﬂow over a cylinder of elliptic cross section when the major axis is horizontal (blunt orientation) or vertical (slender orientation) near forward stagnation point is studied. The unsteadiness is due to an impulsive motion on the free stream. The governing boundary layer equations are ﬁrst reduced into a non-dimensional form, and then transformed into a set of non-similar boundary layer equations, which are solved numerically using an eﬃcient implicit ﬁnite-diﬀerence method known as Keller-Box method. The numerical results are obtained for various values of the Prandtl number, Pr, the mixed convection parameter, α and parameter for blunt and slender orientation, ω. The eﬀects of these parameters on velocity proﬁles,temperature proﬁles as well as Nusselt number are presented through graphs and tables. The results show that as the mixed convection parameter, α is increased, the velocity of the ﬂuid is increased but the temperature of the ﬂuid is decreased, for both blunt and slender orientations. Furthermore, the slender orientation gives earlier separation times for opposing ﬂow while there is no separation of ﬂow detected for the assisting ﬂow.